Activated Immune and Complement C3 Are Potential Contributors in MASH via Stimulating Neutrophil Extracellular Traps - Ao Liu; Xiaoling Deng; Shuhui Hou; Yuwen Xi; Keshu Xu (Cells)
The number of metabolic dysfunction-associated steatotic liver disease (MASLD) patients is increasing rapidly. More attention has been paid to the relationship between immunity and MASLD. This study explored the roles of serum autoantibodies, immunoglobulins, and complements in MASLD. A total of 182 MASLD patients were investigated and grouped by autoantibody or NAS scores. Correlation between immunology and clinical features was assessed. In addition, metabolic dysfunction-associated steatohepatitis (MASH) models were constructed to verify the findings. Neutrophils were isolated from mice and treated with complement C3 to investigate the association between C3 and neutrophil extracellular traps (NETs). IgG, IgM, and NAS scores in the autoantibody positive group were significantly higher than those in the autoantibody negative group. Antinuclear antibodies (ANA), IgA, IgE, IgG, C3, C4, ALT, and AST were related to MASH. Meanwhile, IgA and C3 correlated with the severity of MASLD. The ROC curve showed that IgA > 2.990 g/L or C3 > 1.115 g/L predicted the presence of MASH. More importantly, IgG, activated C3, and NETs were increased in MASH. C3 stimulation directly induced NET formation in the neutrophils. Immunity systems were activated in MASH and elevated IgG activated C3 to stimulate the production of NETs, thus exacerbating MASH.